2020
DOI: 10.12659/msm.926786
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Chinese Version of the Cognitive Distortions Questionnaire (CD-Quest) in College Students

Abstract: Background The aim of this study was to evaluate the reliability and validity of the Chinese version of the Cognitive Distortions Questionnaire (CD-Quest) among Chinese college students. Material/Methods A total of 460 college students from Jining were recruited in the study. Sample 1, including 239 college students, was tested for item analysis and exploratory factor analysis. Sample 2, including 221 college students, was tested for confirmatory factor analysis and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The Chinese version of the Cognitive Distortions Questionnaire(CDQ) [ 48 ] is applied to assess cognitive distortions in terms of both frequency and intensity. The scale is composed of 15 items, and each item is scored on a Likert 4-point (0–3) scale, with frequency ratings ranging from “no time” to “almost all the time” and intensity ratings from “don’t believe” to “believe a lot”.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese version of the Cognitive Distortions Questionnaire(CDQ) [ 48 ] is applied to assess cognitive distortions in terms of both frequency and intensity. The scale is composed of 15 items, and each item is scored on a Likert 4-point (0–3) scale, with frequency ratings ranging from “no time” to “almost all the time” and intensity ratings from “don’t believe” to “believe a lot”.…”
Section: The Studymentioning
confidence: 99%
“…The total score was 0–75; the higher the score, the more obvious the distorted cognition. The Cronbach’s α coefficient and the re-test reliability of this Chinese scale are 0.85 in patients with depression [ 48 ].…”
Section: The Studymentioning
confidence: 99%
“…It provides therapists with a quantitative measure for use in clinical follow-up. 6 The psychometric properties of the CD-Quest have been evaluated in Brazil, 7 the United States, 8 , 9 Australia, 10 Turkey, 11 and China. 12 …”
Section: Introductionmentioning
confidence: 99%
“…In Australia, Kostoglou et al 10 validated the CD-Quest with a sample of 127 university students. Their study observed adequate internal consistency, with Cronbach’s α = 0.80, and significant positive correlations between the CD-Quest and both the ATQ 13 and the Depression Anxiety Stress Scales (DASS).…”
Section: Introductionmentioning
confidence: 99%